Repurposing of FDA‐Approved Drugs for Treating Iatrogenic Botulism: A Paired 3D‐QSAR/Docking Approach†. (9th December 2019) - Floresta, Giuseppe; Patamia, Vincenzo; Gentile, Davide; Molteni, Franco; Santamato, Andrea; Rescifina, Antonio; Vecchio, Michele
Abstract: Botulinum neurotoxin (BoNT) is widely used for the treatment of spasticity, focal dystonia, chronic migraine, facial hemispasm, and facial aesthetic treatments. Generally, treatment with botulinum toxin is a safe procedure when conducted by clinicians with expertise, and local side effects are rare and transient. However, occasionally adverse effects can occur due to the spread of the drug to nontargeted muscles and organs, producing dry mouth, fatigue, and flu‐like symptoms, up to signs of systemic botulism, which appears to be more frequent in children treated for spasticity than in adults. In silico 3D‐QSAR and molecular docking studies were performed to build a structure‐based model on selected potent known botulinum neurotoxin type A inhibitors; this was used to screen the US Food and Drug Administration (FDA) database. Thirty molecules were identified as possible light‐chain BoNT/A inhibitors. In this study, we applied a well‐established ligand‐ and structure‐based methodology for the identification of hit compounds among a database of FDA‐approved drugs. The identification of budesonide, protirelin, and ciclesonide followed by other compounds can be considered a starting point for investigations of selected compounds that could bypass much of the time and costs involved in the drug approval process. Abstract : BoTox safety revisited : The use of botulinum toxin is widely diffused in neurorehabilitation and for aesthetics treatment. Generally, the treatment is a safe procedure but, sometimes, adverse effects such as ptosis could arise by the spread of the drug on nontargeted muscles or organs. Our study identified, among FDA approved drugs, molecules, as budesonide and protirelin, that can potentially block the effect of botulinum toxin, inhibiting the botulinum neurotoxin type A enzyme.